The Teaching on the Four Noble Truths and the Problem of Peace - Srinok, Somchai (International Journal of Multidisciplinary in Management and Tourism, 2020)
Buddhism presents teachings which are the right ways of life. Those teachings have a unique feature; they include the specific teachings and the teachings laid down as a neutral principle that can be fairly applied to every issue. Therefore, teachings in Buddhism cover all fields of knowledge or science dealing with living of human beings including peace. According to the Collection of the Middle Length Sayings, the Buddha told his intention for seeking peace: “Then I, Monks, after a time, being young, my hair coal-black, possessed of radiant youth, in the prime of my life—although my unwilling parents wept and wailed—having cut off my hair and beard, having put on yellow robes, went forth from home into homelessness. I, being gone forth thus, a quester for whatever is good, searching for the incomparable, matchless path to peace, approached Alara the Kalama.”